PENERAPAN PROGRAM SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM PENINGKATAN KEMAMPUAN MANAJEMEN KELAS DI SEKOLAH DASAR - Haryanti, Sri; Fitri Lastini; Anam Sutopo; Sabar Narimo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the implementation of academic supervision programs by school principals in improving teachers' ability to manage classes in elementary schools. Descriptive qualitative research method. The research was conducted at SDN 03 Jatiwarno with the research subjects being the principal supervisor, and teachers as objects of supervision. Data was collected using interview, observation and documentation techniques. Data is analyzed by reducing, presenting and making conclusions. The research results show that this structured and continuous academic supervision program significantly improves teachers' classroom management skills, creates a more conducive learning environment, and supports the achievement of educational goals in elementary schools. The academic supervision program is carried out through three main stages, namely planning, implementation and follow-up. In the planning stage, the principal prepares a supervision plan that includes clear objectives, methods and evaluation criteria. At the implementation stage, direct observation and evaluation are carried out in the classroom to provide constructive feedback to the teacher. The follow-up stage involves providing recommendations and ongoing support to ensure effective implementation of improvements. Thus, the active role of school principals in academic supervision is very important in efforts to improve teacher professionalism and the quality of learning in elementary schools.